Pengaruh Return on Equity dan Current Ratio terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2019-2023 - Ramadhani, Magribi; Lusiana, Lusiana; Sari, Yosi Pupita (Lembaga Yasin AlSys, 2025)
This study aims to analyze the Effect of Return On Equity (ROE) and Current Ratio (CR) on Company Value with Capital Structure as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. This Quantitative Research uses secondary data obtained from the company's financial statements published by the IDX. The population used in this study were all manufacturing companies listed on the IDX during 2019 to 2023 and the Sample was collected using the purposive sampling technique and obtained data from 32 companies for 5 years which were used as research samples. The data analysis technique uses SPSS 26 software and the data analysis method used is multiple linear regression. The results of the analysis show that (1) ROE has a positive and significant effect on Capital Structure. (2) CR has a negative and significant effect on Capital Structure. (3) ROE has a negative and significant effect on Company Value. (4) CR has a negative and significant effect on Company Value. (6) The intervening variable Capital Structure does not mediate the ROE variable on Company Value. (7) The intervening variable Capital Structure does not mediate CR on Company Value. This study contributes to the understanding of the factors that influence the Company Value of manufacturing companies in Indonesia and the importance of Capital Structure in optimizing company value.